IMPROVING THE STUDENTS’ ACHIEVEMENT ON WRITING DESCRIPTIVE TEXT BY USING REALIA - Ika Afridah; Siti Aisyah Ginting (Universitas Negeri Medan, 2012)
Students’ achievement in writing descriptive text is very low, in this study Realia was applied to solve the problem. Action research in conducted for the result and the technique to collect the data, qualitative and quantitative are applied in this research. The subject of this research is grade VII in Junior High School (SMP N 2 ) Kisaran. In the first evaluation (66, 2926) increased to the mean of second evaluation (76, 7560) and the mean of third evaluation (87, 0243). Observation result showed that the students gave their good attitudes and responses during teaching and learning process by applying the application of Realia. Questionnaire and interview report showed that students agree that the application of Realia had helped them in writing descriptive text. It can be conclude that the students’ achievement is improved when thay are tought through Realia. Key Words: Achievement, Writing, Descriptive Text and Realia